Immunometabolic responses according to physical fitness status and lifelong exercise during aging: New roads for exercise immunology - Padilha, Camila S. [UNESP]; Figueiredo, Caique [UNESP]; Minuzzi, Luciele Guerra [UNESP]; Chimin, Patricia; Deminice, Rafael; Krüger, Karsten; Rosa-Neto, José Cesar; Lira, Fabio Santos [UNESP] (Elsevier, 2021)
Molecules such as cytokines, energetic substrates, and hormones found in the immune cell environment, especially lymphocytes and monocytes, are crucial for directing energy metabolism. In turn, changes in energy metabolism occur in a synchronized manner with the activation of certain signaling pathways, thereby this crosstalk is responsible for determining the functionality of immune cells. The immunometabolism field has grown over time and that is becoming increasingly promising in several populations; here we discuss the mechanisms involved in sedentary and physically active middle-aged individuals and master athletes. In this context, this review shows that the physical activity status and lifelong exercise seems to be good strategies for the promotion of metabolic and functional adaptations in T lymphocytes and monocytes, counteracting inflammatory environments caused by expanded adipose tissue and sedentary behavior, as well as delaying the immunosenescence caused by aging.
Keywords: Body adiposity; Cardiorespiratory fitness; Immunometabolism; Inflammation; Physical exercise